Potensi Likuifaksi Tanah Pasir Diatas Tanah Lunak Dengan Variasi Jenis Tanah Lunak Melalui Uji Model Laboratorium - Erik Azarya Ginting; Agus Ika Putra; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In each region has a different type of soft soil, for example peat soils, soft silt soils and soft clay. Pekanbaru, the capital of Riau Province, located on the island of Sumatra where the island of Sumatra itself is an area that has a high intensity earthquake because it is located in the ring of fire. One of the earthquake impact is liquefaction. Liquefaction is a phenomenon in which the strength and stiffness of soil is reduced due to an earthquake or other earth movement. This is a process of changing the nature of the soil from solid state to a liquid state. The aim of this research to figure out the influence of soft soil variation as the native layer of sand embankment and acceleration of vibration against increase of pore water pressure and soil settlement. This research was conducted by laboratory model test using shaking table. Variations of soft soil under sand embankment used are peat soil, soft silt soil and soft clay respectively 10 cm thick and given a uniform load of 40kg / m2. Water level elevation as thick as the sand layer of each variation. The test results showed that silt soil has the largest soil settlement and pore water increase. Silt soil variation tends to require a short period to reach maximum soil sttlement during liquefaction. As the acceleration of vibration increase caused larger soil settlement and pore water pressure, but it required faster time for pore water pressure to stable.Keyword: Liquefaction, shaking table, peat,silt,clay,embankment